Mengkonsumsi Simbol Ala Thrifting Hunter di Kota Banjarmasin - Resdawati, Resdawati; Hidayah, Sri (Huma: Jurnal Sosiologi, 2024)
Nowadays, the trend of buying used clothes or thrifting is popular among the people of Banjarmasin City. This research aims to find out the factors that influence the people of Banjarmasin City in buying used clothes, as well as how symbols (brands) affect the thrifting hunter's lifestyle when buying and using them. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interview, and documentation. The data analysis was done interactively through the process of data reduction, data presentation and conclusion drawing. The results of this study show that the thrifting phenomenon affects consumption patterns in fulfilling people's lifestyles, which no longer consume based on utility but rather prioritise the signs or symbols attached to an item. Factors that influence the people of Banjarmasin City in consuming used clothing are: 1) individual factors, namely economy, self-existence, and thrifting as a hobby; 2) social factors, namely family and social status; and, 3) cultural factors, namely the influence of social media and idol artists. Analysed based on the theory of consumption society through the analysis of the social logic of consumption (Baudrillard, 2011), it is concluded that there is happiness, enjoyment and freedom for a thrifting hunter when buying and using second-hand clothes, or being able to fulfil lifestyle desires. Suggestions for the people of Banjarmasin City, especially for users of second-hand clothes, to be more selective in considering a decision in buying second-hand clothes. Buying because of a desire rather than a need that occurs continuously results in waste and inefficiency in buying an product.